2009
DOI: 10.1080/15256480802557275
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Uncertainty and Scanning Behavior: An Assessment of Top-Level Hotel Executives

Abstract: Serious concern by hoteliers pertaining to how managers' perceptions of environmental uncertainty may influence the incidence and scope of environmental scanning in the company's strategy formulation process has not been matched by appropriate research in the area. It has been argued that objective measures of the instability, or volatility associated with the heterogeneous and diverse hospitality business environment may be less strongly related to the strategy-making process than subjective perceptions to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 102 publications
(174 reference statements)
0
13
0
Order By: Relevance
“…Lashgari (2015) mentions that investors via managing their emotions, could keep an acceptable level of performance. In the hospitality industry, which is characterized by environmental uncertainty (see, among others, Jogaratnam & Wong, 2009), emotionally intelligent employees may show creative performance by forming an emotional relationship with customers and thus overcome environmental uncertainty. Ezzi et al (2016) show that emotionally intelligent leaders, through forecasting and adapting themselves to the environmental changes, are more capable of solving problems and effectively developing strategies for employees and customers.…”
Section: Environmental Uncertainty As a Mediatormentioning
confidence: 99%
“…Lashgari (2015) mentions that investors via managing their emotions, could keep an acceptable level of performance. In the hospitality industry, which is characterized by environmental uncertainty (see, among others, Jogaratnam & Wong, 2009), emotionally intelligent employees may show creative performance by forming an emotional relationship with customers and thus overcome environmental uncertainty. Ezzi et al (2016) show that emotionally intelligent leaders, through forecasting and adapting themselves to the environmental changes, are more capable of solving problems and effectively developing strategies for employees and customers.…”
Section: Environmental Uncertainty As a Mediatormentioning
confidence: 99%
“…Even though managers below top executive levels typically conduct scanning more frequently (Hambrick 1981), strategy making is linked to subjective interpretations in difficult to comprehend and rapidly changing environments (Elenkov 1997;Jogaratnam and Wong 2009;Hambrick 1981). A proactive stance is further inhibited when top executives assume that lower level executives are performing scanning, when in fact they are not (Hambrick 1981).…”
Section: Types Of Scanningmentioning
confidence: 99%
“…Data completeness and analyzability influences sense-making (Sutcliffe 1994). Proactively, data structures must assist with the processing needed to develop, pursue, and monitor a strategy (Choo 2001;Jogaratnam and Wong 2009;Lau et al 2012). Otherwise, leaders may decide an environment is unanalyzable, avoiding it at their own peril (Aguilar 1967;Ferrier et al 1999).…”
Section: Scanning Success Factorsmentioning
confidence: 99%
“…The first notable study of environmental scanning by Aguilar (1967) defined the process as "scanning for information about events and relationships in a company's outside environment, the knowledge of which would assist top management in its task of charting the company's future course of action" (p. vii). The research on environmental scanning has traditionally focused on individual, large, for-profit firms although the technique has been successfully applied across an ever wider range of organizations, including public leisure agencies (Bartlett & McKinney, 2004) and in tourism and hospitality settings that have included restaurants (West & Olson, 1989), hotels (Jogaratnam & Wong, 2009), and country clubs (Gustafson & Partlow, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, they found that the major sources of environmental scanning information for strategic planning used by country clubs were often limited to planning committees, boards, colleagues, consultants, and professional associations. More recently, Jogaratham and Wong (2009) found that hotel executives in Hong Kong tended to scan with greater frequency and more broadly when they perceived increased uncertainty in the external environment. Although there has been an increase in strategic planning and environmental scanning in hospitality and tourism organizations (Okumus, 2004) there remains very little research focused on scanning for human resource planning.…”
Section: Literature Reviewmentioning
confidence: 99%